Conferences 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
ConferencesContributions of science to the development of forest policies7 - 9 January 1999, South AfricaThe purpose of this meeting is to provide a forum for dialogue on the integration of science and forest policy. There are many experiments going...